Preparation method and application of zinc-bromine flow battery positive electrode material

By employing a multi-level composite design on the cathode material of a zinc-bromine flow battery, consisting of a three-dimensional porous carbon substrate, a metal nitride nanocrystal array, Sn-Bi bimetallic nanoparticles, and a polyaniline-bromine complex layer, the problems of unfixed Br2 and slow Br2/Br- redox reaction in zinc-bromine flow batteries were solved, achieving high-efficiency electrochemical performance and structural stability, and improving the overall performance of the battery.

CN121484093APending Publication Date: 2026-02-06SHANDONG HAIHUA GRP CO LTD +1

Patent Information

Application Number
CN202511390751.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-26
Publication Date
2026-02-06

AI Technical Summary

Technical Problem

In zinc-bromine flow batteries, the Br2 generated at the positive electrode during charging is not fixed, leading to self-discharge and loss of active materials. Furthermore, the sluggish kinetics of the Br2/Br- redox reaction limits the battery's high current density performance. In existing technologies, the introduction of ionic liquids and binders hinders electron conduction at the positive electrode and causes capacity decay.

Method used

By employing in-situ growth of metal nitride nanocrystal arrays and Sn-Bi bimetallic nanoparticles on a three-dimensional porous carbon substrate, combined with a multi-level composite design of polyaniline-bromine complex layers, and through plasma cleaning, oxygen/argon etching, and chemical vapor deposition techniques, the reaction conditions and material ratios are optimized to improve conductivity, catalytic activity, and structural stability.

Benefits of technology

It significantly improves the conductivity and catalytic activity of the cathode material in zinc-bromine flow batteries, reduces the activation energy of the Br2/Br- redox reaction, suppresses the bromine shuttle effect, and improves the coulombic efficiency, voltage efficiency, and energy efficiency of the battery, meeting the requirements for high current density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121484093A_ABST
    Figure CN121484093A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a zinc-bromine flow battery positive electrode material, and belongs to the field of zinc-bromine flow batteries. The preparation method comprises the following steps: firstly, cleaning and activating a carbon-based three-dimensional conductive network substrate by adopting plasmas, performing oxygen / argon plasma etching, and performing chemical vapor deposition on carbon to prepare three-dimensional porous carbon; then growing a metal oxide nanocrystalline array on the three-dimensional porous carbon by a hydrothermal method, and carrying out ammonia gas calcination to convert the metal oxide nanocrystalline array into a metal nitride nanocrystalline array; then preparing an electro-deposition solution containing tin bismuth salt and an aniline-bromine source polymerization solution, and constructing Sn-Bi bimetallic nanoparticles and a polyaniline-bromine complex layer on the metal nitride nanocrystalline array / three-dimensional porous carbon precursor through electro-deposition and electro-polymerization in sequence to finally prepare the high-performance zinc-bromine battery positive electrode material. The positive electrode material has high conductivity, excellent Br2 / Br <-> catalytic activity and structural stability, and the coulombic efficiency, the voltage efficiency and the energy efficiency of the battery are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of zinc-bromine flow batteries, specifically relating to a method for preparing and applying a positive electrode material for zinc-bromine flow batteries. Background Technology

[0002] With the rapid expansion of global renewable energy (such as wind power and photovoltaics) installed capacity, the intermittency and volatility of its power generation pose a severe challenge to grid stability, necessitating systems with long-term energy storage capabilities to achieve time-shifted and smooth output of electrical energy. Zinc-bromine flow batteries, based on the reversible redox reaction of zinc and bromine, use an aqueous zinc bromide solution as the electrolyte. Through electrolyte circulation, power and capacity are decoupled, achieving a theoretical energy density of 435 Wh / kg. Furthermore, the electrolyte raw materials (zinc and bromine) are abundant and inexpensive (approximately 1 / 5 the cost of vanadium redox flow batteries). The aqueous system also offers high safety and environmental friendliness, making it suitable for grid peak shaving, renewable energy grid integration, and distributed energy storage scenarios. However, its industrialization still faces multiple technical bottlenecks: First, the high chemical reactivity of elemental bromine (Br2) easily triggers electrode corrosion and membrane degradation. Especially during charging, if the Br2 generated at the positive electrode is not fixed, it will penetrate the porous ion exchange membrane and react with the zinc negative electrode (shuttle effect), leading to self-discharge and loss of active materials, significantly reducing coulombic efficiency. In addition, the Br2 / Br... - The sluggish kinetics of redox reactions limit the high current density performance of batteries, especially on the positive electrode side. The reduction rate of Br2 is limited by the insufficient number of active sites on the positive electrode surface, leading to increased polarization loss at high current densities. Chinese patent document CN119108566A discloses a method for modifying zinc-bromine battery positive electrode materials with an ionic liquid bromine complexing agent. This technology changes the ionic liquid from an electrolyte additive to direct modification on the positive electrode surface, using a binder for fixation, thus improving the bromine species fixation effect and reducing the shuttle effect. However, the introduction of ionic liquid and binder hinders electron conduction at the positive electrode, and the ionic liquid may detach from the positive electrode during cycling, leading to capacity decay. Summary of the Invention

[0003] This invention provides a method for preparing a positive electrode material for a zinc-bromine flow battery and its application. The preparation method of this invention can significantly improve the conductivity, catalytic activity and stability of the positive electrode material. The preparation method is simple and can significantly improve the overall performance of the battery, and has broad prospects for industrial application.

[0004] To solve the above-mentioned technical problems, the present invention provides the following technical solution: This invention provides a method for preparing a positive electrode material for a zinc-bromine flow battery, comprising the following steps: (1) The carbon-based three-dimensional conductive network substrate is cleaned by inert gas plasma. After cleaning, oxygen / argon plasma is introduced for etching. Then, the etched carbon-based three-dimensional conductive network substrate is subjected to chemical vapor deposition of carbon. The organic gas carbon source used is alkanes, alkenes or alkynes to obtain a three-dimensional porous carbon substrate. (2) The three-dimensional porous carbon substrate obtained in step (1) is immersed in a mixed aqueous solution containing transition metal salt, hydrolysis ammonia-producing precipitant and neutral or weakly alkaline salt mineralizer for hydrothermal treatment; the treated three-dimensional porous carbon substrate is taken out, washed with deionized water or ethanol and dried to obtain metal oxide nanocrystal array / three-dimensional porous carbon precursor. (3) The metal oxide nanocrystal array / three-dimensional porous carbon precursor obtained in step (2) is calcined under an ammonia atmosphere to obtain a metal nitride nanocrystal array / three-dimensional porous carbon precursor. (4) Dissolve tin salt, bismuth salt and complexing additive in acidic aqueous solution to obtain a homogeneous soaking solution; (5) Dissolve aniline and bromine source in acidic aqueous solution to obtain a homogeneous complex solution; (6) Using the three-electrode technology, the metal nitride nanocrystal array / three-dimensional porous carbon precursor obtained in step (3) is used as the working electrode. It is immersed in the soaking solution obtained in step (4) for electrodeposition. After deposition, the working electrode is immersed in the homogeneous complexing solution obtained in step (5) for electropolymerization. After completion, it is cleaned with deionized water or ethanol and dried to obtain the zinc bromine flow battery cathode material.

[0005] Preferably, in step (1), the carbon-based three-dimensional conductive network substrate is one of carbon fiber felt, graphite felt, carbon cloth, and carbon paper; the inert gas plasma is argon or nitrogen; the plasma cleaning power is 200-300W; the cleaning time is 5-10min; the volume ratio of oxygen to argon is 1:3-5; the plasma etching power is 300-500W; the etching time is 20-60min; the alkane, olefin, or alkyne organic gas carbon source is one of methane, ethane, ethylene, and acetylene; the alkane, olefin, or alkyne organic gas carbon source flow rate is 20-60mL / min; the vapor deposition carbon temperature is 750-850℃; and the time is 1-4h.

[0006] Preferably, in step (2), the transition metal salt is one of titanium chloride, aluminum chloride, and zinc nitrate; the hydrolysis-induced ammonia-producing precipitant is one or more of hexamethylenetetramine and urea; and the neutral or weakly alkaline salt mineralizer is one of sodium chloride, potassium chloride, and sodium acetate. The concentration of the transition metal salt is 0.05–0.2 M, the molar ratio of the transition metal salt to the hydrolysis-induced ammonia-producing precipitant is 1:3.5–7, the molar ratio of the transition metal salt to the neutral or weakly alkaline salt mineralizer is 1:1.5–4, the hydrothermal treatment temperature is 150–180 °C, and the time is 5–8 h.

[0007] Preferably, in step (3), the calcination temperature is 700-900℃ and the time is 1-3h.

[0008] Preferably, in step (4), the tin salt is stannous sulfate or stannous chloride, the bismuth salt is bismuth nitrate or bismuth chloride, the complexing additive is one of sodium citrate, ethylenediaminetetraacetic acid, or ammonium fluoride, and the acidic aqueous solution is an aqueous solution of sulfuric acid or hydrochloric acid; the molar concentration of the bismuth salt is 0.05-0.15 M, the molar ratio of bismuth salt to tin salt is 1:1-3, the molar ratio of the complexing additive to bismuth salt is 1:3-10, and the molar concentration of acid in the acidic aqueous solution is 0.5-1.5 M.

[0009] Preferably, in step (5), the bromine source is one of tetrabutylammonium bromide, sodium bromide, and potassium bromide, and the acidic aqueous solution is one of sulfuric acid and hydrochloric acid aqueous solution; the molar concentration of aniline is 0.05-0.2M, the molar ratio of bromine source to aniline is 1:4-8, and the molar concentration of acidic aqueous solution is 0.5-1M.

[0010] Preferably, in step (6), the electrodeposition current density is 5–15 mA / cm². 2 The time is 5–10 min; the electropolymerization current density is 0.2–1 mA / cm². 2 The time is 10 to 30 minutes.

[0011] The present invention also provides the application of the prepared zinc-bromine flow battery cathode material in the cathode of a zinc-bromine battery.

[0012] The beneficial effects of this invention are as follows: 1. The technical solution of this invention utilizes a multi-level composite design, including three-dimensional porous carbon, metal nitride nanocrystal array, Sn-Bi bimetallic nanoparticles, and polyaniline-bromine complex layer, to precisely control reaction conditions and material ratios, thereby achieving synergistic effects among the components and preparing a zinc-bromine flow battery cathode material with high conductivity, excellent Br2 / Br⁻ catalytic activity, and structural stability.

[0013] 2. The technical solution of this invention utilizes chemical vapor deposition (CVD) technology to generate porous carbon in situ on the surface of a carbon-based three-dimensional conductive network substrate using alkane, olefin, or alkyne carbon sources. This porous carbon provides abundant sites for subsequent loading of metal nitride nanocrystals, tin-bismuth alloys, and polyaniline-bromine complex layers. Furthermore, its unique microporous and mesoporous structure achieves a balance between rapid electrolyte wetting (micropores) and efficient diffusion of bromide ions / polybromines (mesoporosis). Therefore, this structure can significantly reduce the activation energy of the Br2 / Br⁻ redox reaction and improve reaction kinetics. In addition, argon plasma treatment can introduce microporous structures onto the surface of the carbon-based three-dimensional conductive network substrate, significantly enhancing the anchoring effect of carbon deposition during subsequent vapor deposition. The oxygen-containing functional groups introduced by oxygen etching not only enhance the affinity between the cathode material and the aqueous electrolyte, but also suppress the free diffusion of polybrominated ions through hydrogen bonding, reducing self-discharge losses. At the same time, the three-dimensional porous carbon has excellent conductivity and mechanical stability, ensuring the electrochemical performance stability and structural stability of the cathode during charge-discharge cycles, which can meet the high current density requirements of zinc-bromine flow batteries.

[0014] 3. The technical solution of this invention achieves multi-scale synergistic enhancement by in-situ growing a metal nitride nanocrystal array on the surface of a three-dimensional porous carbon substrate: the highly active crystal faces exposed by the nanocrystals significantly improve the catalytic efficiency of the Br2 / Br⁻ redox reaction; the high conductivity of the nitrides and the three-dimensional continuous conductive network formed by the three-dimensional porous carbon can effectively reduce the interfacial charge transfer resistance; the gaps between the nanocrystals serve as physical confinement channels for the polybrominated compounds, suppressing the bromine shuttle effect through capillary action; the strong metal-nitrogen covalent bonds formed by the nitriding treatment endow the nanocrystals with excellent chemical stability and corrosion resistance, enhancing the structural stability of the cathode material, thereby improving the overall performance of the battery.

[0015] 4. The technical solution of this invention adopts a Sn-Bi bimetallic nanoparticle system, which synergistically optimizes battery performance: In terms of conductivity, Sn's high conductivity significantly reduces the interfacial resistance of the positive electrode, while Bi's electronic structure regulation further optimizes the charge transfer path, greatly improving the battery's energy efficiency; secondly, in terms of catalytic activity, the Sn-Bi bimetallic nanoparticles generate abundant active sites, which can lower the energy barrier of the bromine redox reaction, thereby improving charge and discharge efficiency; in terms of suppressing bromine shuttle, Sn anchors bromine molecules through strong chemical bonding, while Bi further enhances this anchoring effect to suppress bromine shuttle; in addition, the high corrosion resistance of the Sn-Bi bimetallic system can protect the metal nitride nanocrystal array and the three-dimensional porous carbon from bromine chemical corrosion, extending the cycle life of the positive electrode. This synergistic design achieves unified optimization of conductivity, catalytic activity, and stability.

[0016] 5. The technical solution of this invention involves electropolymerizing aniline and a bromine source on the surface of Sn-Bi bimetallic nanoparticles and metal nitride nanocrystal arrays to generate a polyaniline-bromine complex layer in situ. During this process, the electropolymerization of aniline to form polyaniline enhances the adsorption capacity for polybrominates, significantly reducing the bromine shuttle effect. Furthermore, polyaniline protects the metal nitride nanocrystals and Sn-Bi bimetallic nanoparticles, improving the structural stability of the cathode material. The polyaniline-bromine complex layer not only immobilizes polybrominates through both chemical bonding and physical adsorption, effectively suppressing the diffusion of Br2 / Br⁻, but also utilizes the flexible properties of the polyaniline-bromine complex layer to buffer the volume changes of the cathode during charging and discharging, thereby preventing cracking of the cathode structure.

[0017] 6. The technical solution of this invention achieves significant improvement in the modification of cathode materials and battery performance by optimizing key process parameters. These include, for example, plasma cleaning, oxygen / argon etching, type of organic gas, chemical vapor deposition temperature, ammonia treatment, electrochemical deposition parameters, and electropolymerization parameters. Plasma cleaning removes surface impurities and oxide layers, exposing active sites and improving the adhesion of subsequent etching and deposition. During oxygen / argon mixed gas etching, controlling the oxygen to argon volume ratio to 1:3–5 allows argon to physically bombard the cathode material, introducing microporous structures onto the material surface. This process significantly enhances the anchoring effect of carbon deposition during subsequent vapor deposition. Simultaneous introduction of oxygen can introduce oxygen-containing functional groups (such as -OH and -COOH) to enhance surface hydrophilicity and chemical activity, and effectively remove organic contaminants and oxide layers from the substrate surface, creating favorable conditions for the uniform loading of nanocrystals. Selecting a suitable type of organic gas can avoid the formation of highly graphitized carbon layers, contributing to sufficient micropores and high surface polarity, meeting the requirements of zinc-bromine battery cathode materials for bromine adsorption, ion transport, and structural stability. Furthermore, due to its low H / C ratio and controllable decomposition pathway, directional carbon generation can be achieved without byproduct contamination. Controlling the chemical vapor deposition temperature at 750–850℃ facilitates the decomposition of organic gases into carbon atoms, which are then uniformly deposited on the etched substrate surface. The metal nitride nanocrystal array / three-dimensional porous carbon precursor obtained through ammonia treatment exhibits superior conductivity, catalytic activity, and chemical stability compared to oxide nanocrystal array / three-dimensional porous carbon precursors, resulting in better battery performance. Controlling the electrochemical deposition current density to 5–15 mA / cm² is also crucial. 2 And the electropolymerization current density is 0.2–1 mA / cm². 2 It can achieve uniform distribution of Sn-Bi bimetallic nanoparticles and polyaniline-bromine complex layers, thereby improving the overall performance of the battery.

[0018] 7. The three-dimensional porous carbon, metal nitride nanocrystal array, Sn-Bi bimetallic nanoparticles, and polyaniline-bromine complex layer in the zinc-bromine flow battery cathode material of this invention work synergistically through their respective characteristics and interactions, improving the electrochemical activity of the prepared zinc-bromine cathode material and ultimately enhancing the overall performance of the battery. The zinc-bromine flow battery cathode material prepared by the method of this invention exhibits outstanding performance in zinc-bromine battery applications. At a current density of 20 mA / cm²... 2 Under these conditions, the coulombic efficiency is as high as 96.2-96.7%, the voltage efficiency is as high as 85.8-86.6%, and the energy efficiency is as high as 82.5-83.7%. Attached Figure Description

[0019] Figure 1 The image shows a scanning electron microscope (SEM) image of the zinc-bromine flow battery cathode material prepared in Example 1. Figure 2 The pore size distribution diagram is shown for the zinc-bromine flow battery cathode material prepared in Example 1. Figure 3 The pore size distribution of the zinc-bromine flow battery cathode material prepared for Comparative Example 3 is shown in the diagram. Detailed Implementation

[0020] The principles and features of the present invention are described below. The embodiments and comparative examples are for illustrative purposes only and are not intended to limit the scope of the invention. Unless otherwise specified, specific conditions in the embodiments are performed under conventional conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products. Example 1

[0021] (1) The carbon fiber felt substrate was cut into 2cm×2cm size, and then the carbon fiber felt was placed in a vacuum plasma reaction chamber. 50sccm of high-purity argon gas was introduced, and the radio frequency power was set to 200W for 10min for argon gas cleaning. Then the argon gas was turned off, and the oxygen and argon mixed gas (volume ratio of 1:3, O2:Ar=25sccm:75sccm) was introduced. The radio frequency power was increased to 400W and etching was carried out for 40min. After etching was completed, the carbon fiber felt was transferred to a tubular furnace reactor and heated to 800℃ at a heating rate of 10℃ / min. Acetylene was introduced at 60mL / min as carbon source gas for 1h chemical vapor deposition to obtain a three-dimensional porous carbon substrate. (2) The three-dimensional porous carbon substrate was immersed in a pre-prepared mixed aqueous solution, which consisted of 1.54 g titanium chloride, 3.0 g urea and 1.75 g sodium chloride in 100 ml. The immersed three-dimensional porous carbon substrate was transferred to a high-pressure reactor lined with polytetrafluoroethylene, sealed and placed in an oven at 160 ℃ for hydrothermal treatment for 6 h. After the reaction was completed, it was naturally cooled to room temperature, the three-dimensional porous carbon substrate was taken out and rinsed repeatedly with deionized water 3 times to remove surface residues. Finally, the sample was placed in a vacuum drying oven at 80 ℃ for 8 h to obtain titanium oxide nanocrystal array / three-dimensional porous carbon precursor; (3) The precursor was loaded into a ceramic boat and placed in a calcining furnace. Then, under an ammonia atmosphere, the temperature was slowly increased to 800°C at a rate of 5°C / min and held at this temperature for 2 hours to obtain a titanium nitride nanocrystal array / three-dimensional porous carbon precursor. (4) Dissolve 2.15g stannous sulfate, 3.95g bismuth nitrate and 0.86g sodium citrate in 200mL of 1M sulfuric acid aqueous solution, and stir continuously until completely dissolved to obtain a homogeneous soaking solution; (5) Dissolve 1.86 g aniline and 1.33 g tetrabutylammonium bromide in 200 mL of 0.6 M sulfuric acid aqueous solution to obtain a homogeneous complex solution; (6) A three-electrode technique was adopted, using a titanium nitride nanocrystal array / three-dimensional porous carbon precursor as the working electrode, Ag / AgCl as the reference electrode, and a platinum sheet as the counter electrode. The electrodeposition was carried out by immersing the substrate in a pre-prepared immersion solution, and the electrodeposition current density was controlled to be 10 mA / cm². 2 The duration was 5 minutes. After electrodeposition, the working electrode was removed from the immersion solution and immersed in a pre-prepared complexing solution for electropolymerization. The electropolymerization current density was set to 0.2 mA / cm². 2 The reaction time was 30 min. After the electropolymerization reaction was completed, the working electrode was removed from the complexing solution and thoroughly cleaned with deionized water to remove residual reactants and impurities on the surface. The cleaned electrode was then placed in a drying oven and dried at 80°C for 10 h to obtain the zinc-bromine battery cathode material. Example 2

[0022] (1) The graphite felt substrate was cut to a size of 2cm×2cm, and then the graphite felt was placed in a vacuum plasma reaction chamber. 50sccm of high-purity argon gas was introduced, and the radio frequency power was set to 250W for 8min for argon gas cleaning. Then the argon gas was turned off, and the oxygen and argon mixed gas (volume ratio of 1:3, O2:Ar=25sccm:75sccm) was introduced. The radio frequency power was increased to 300W and the etching was continued for 60min. After the etching was completed, the graphite felt was transferred to a tubular furnace reactor and heated to 850℃ at a heating rate of 5℃ / min. 20mL / min of methane was introduced as the carbon source gas for 2h chemical vapor deposition to obtain a three-dimensional porous carbon substrate. (2) The three-dimensional porous carbon substrate was immersed in a pre-prepared mixed aqueous solution, which consisted of 1.33 g aluminum chloride, 2.1 g urea and 3.28 g sodium acetate in 50 ml. The immersed three-dimensional porous carbon substrate was transferred to a high-pressure reactor lined with polytetrafluoroethylene, sealed and placed in an oven at 150 °C for hydrothermal treatment for 7 h. After the reaction was completed, the substrate was naturally cooled to room temperature, and the three-dimensional porous carbon substrate was removed. It was rinsed three times with deionized water to remove surface residues. Finally, the sample was placed in a vacuum drying oven at 80 °C for 6 h to obtain an alumina nanocrystal array / three-dimensional porous carbon precursor. (3) The precursor was loaded into a ceramic boat and placed in a calcining furnace. Then, under an ammonia atmosphere, the temperature was slowly increased to 750°C at a rate of 10°C / min and held at this temperature for 3 hours to obtain an aluminum nitride nanocrystal array / three-dimensional porous carbon precursor. (4) Dissolve 1.9g stannous sulfate, 3.15g bismuth chloride and 0.29g ethylenediaminetetraacetic acid in 200mL of 0.5M sulfuric acid aqueous solution in sequence, and stir continuously until completely dissolved to obtain a homogeneous soaking solution; (5) Dissolve 0.93g aniline and 0.13g sodium bromide in 200mL of 0.5M hydrochloric acid aqueous solution to obtain a homogeneous complex solution; (6) A three-electrode technique was adopted, using an aluminum nitride nanocrystal array / three-dimensional porous carbon precursor as the working electrode, Ag / AgCl as the reference electrode, and a platinum sheet as the counter electrode. The electrodeposition was carried out by immersing the substrate in a pre-prepared immersion solution, and the electrodeposition current density was controlled at 12 mA / cm². 2 The duration was 5 minutes. After electrodeposition, the working electrode was removed from the immersion solution and immersed in a pre-prepared complexing solution for electropolymerization. The electropolymerization current density was set to 0.5 mA / cm². 2 The reaction time was 25 min. After the electropolymerization reaction was completed, the working electrode was removed from the complexing solution and thoroughly cleaned with deionized water to remove residual reactants and impurities on the surface. The cleaned electrode was then placed in a drying oven and dried at 60°C for 8 h to obtain the zinc-bromine battery cathode material. Example 3

[0023] (1) The carbon paper was cut into 2cm×2cm sizes, and then placed in a vacuum plasma reaction chamber. 50sccm of high-purity nitrogen gas was introduced, and the radio frequency power was set to 300W for 5min for nitrogen cleaning. Then the nitrogen gas was turned off, and a mixture of oxygen and argon gas (volume ratio of 1:4, O2:Ar=20sccm:80sccm) was introduced. The radio frequency power was increased to 500W and etching was carried out for 20min. After etching was completed, the carbon paper was transferred to a tubular furnace reactor and heated to 800℃ at a heating rate of 8℃ / min. 30mL / min of ethylene was introduced as the carbon source gas for 3h chemical vapor deposition to obtain a three-dimensional porous carbon substrate. (2) The three-dimensional porous carbon substrate was immersed in a pre-prepared mixed aqueous solution, which consisted of 1.42 g zinc nitrate, 2.45 g hexamethylenetetramine, 2.1 g urea and 0.83 g potassium chloride. The immersed three-dimensional porous carbon substrate was transferred to a high-pressure reactor lined with polytetrafluoroethylene, sealed and placed in an oven at 180°C for hydrothermal treatment for 5 h. After the reaction was completed, the substrate was naturally cooled to room temperature, and the three-dimensional porous carbon substrate was removed. It was rinsed three times with ethanol to remove surface residues. Finally, the sample was placed in a vacuum drying oven at 60°C for 10 h to obtain a zinc oxide nanocrystal array / three-dimensional porous carbon precursor. (3) The precursor was loaded into a ceramic boat and placed in a calcining furnace. Then, under an ammonia atmosphere, the temperature was slowly increased to 900°C at a rate of 10°C / min and held at that temperature for 1 hour to obtain zinc nitride nanocrystal array / three-dimensional porous carbon precursor. (4) Dissolve 5.69g stannous chloride, 9.46g bismuth chloride and 0.22g ammonium fluoride in 200mL of 1.5M hydrochloric acid aqueous solution in sequence, and stir continuously until completely dissolved to obtain a homogeneous soaking solution; (5) Dissolve 3.72g aniline and 0.82g sodium bromide in 200mL of 1M sulfuric acid aqueous solution to obtain a homogeneous complex solution; (6) A three-electrode technique was adopted, using a zinc nitride nanocrystal array / three-dimensional porous carbon precursor as the working electrode, Ag / AgCl as the reference electrode, and a platinum sheet as the counter electrode. The electrodeposition was carried out by immersing the substrate in a pre-prepared immersion solution, and the electrodeposition current density was controlled to be 5 mA / cm². 2 The duration is 10 minutes. After electrodeposition, the working electrode is removed from the immersion solution and immersed in a pre-prepared complexing solution for electropolymerization. The electropolymerization current density is set to 1 mA / cm². 2The reaction time was 10 min. After the electropolymerization reaction was completed, the working electrode was removed from the complexing solution and thoroughly cleaned with ethanol to remove residual reactants and impurities on the surface. The cleaned electrode was then placed in a drying oven and dried at 100°C for 6 h to obtain the zinc-bromine battery cathode material. Example 4

[0024] (1) The carbon cloth was cut to a size of 2cm×2cm, and then the carbon was arranged in a vacuum plasma reaction chamber. 50sccm of high-purity nitrogen was introduced, and the radio frequency power was set to 300W for 8min for nitrogen cleaning. Then the nitrogen was turned off, and a mixture of oxygen and argon gas (volume ratio of 1:4, O2:Ar=20sccm:80sccm) was introduced. The power was kept constant and the etching was continued for 30min. After the etching was completed, the carbon cloth was transferred to a tubular furnace reactor and heated to 750℃ at a heating rate of 10℃ / min. 40mL / min of ethane was introduced as the carbon source gas for chemical vapor deposition for 4h to obtain a three-dimensional porous carbon substrate. (2) The three-dimensional porous carbon substrate was immersed in a pre-prepared mixed aqueous solution, which consisted of 3.08 g titanium chloride, 4.8 g urea and 2.33 g sodium chloride in 200 ml. The immersed three-dimensional porous carbon substrate was transferred to a high-pressure reactor lined with polytetrafluoroethylene, sealed and placed in an oven at 180 ℃ for hydrothermal treatment for 5 h. After the reaction was completed, the substrate was naturally cooled to room temperature, the three-dimensional porous carbon substrate was removed and rinsed three times with ethanol to remove surface residues. Finally, the sample was placed in a vacuum drying oven at 100 ℃ for 6 h to obtain a titanium oxide nanocrystal array / three-dimensional porous carbon precursor. (3) The precursor was loaded into a ceramic boat and placed in a calcining furnace. Then, under an ammonia atmosphere, the temperature was slowly increased to 700°C at a rate of 2°C / min and held at this temperature for 2 hours to obtain a titanium nitride nanocrystal array / three-dimensional porous carbon precursor. (4) Dissolve 11.38g stannous chloride, 7.9g bismuth nitrate and 0.25g ammonium fluoride in 200mL of 1.2M hydrochloric acid aqueous solution in sequence, and stir continuously until completely dissolved to obtain a homogeneous soaking solution; (5) Dissolve 2.79 g aniline and 0.60 g potassium bromide in 200 mL of 0.8 M hydrochloric acid aqueous solution to obtain a homogeneous complex solution; (6) A three-electrode technique was adopted, using a titanium nitride nanocrystal array / three-dimensional porous carbon precursor as the working electrode, Ag / AgCl as the reference electrode, and a platinum sheet as the counter electrode. The electrodeposition was carried out by immersing the substrate in a pre-prepared immersion solution, and the electrodeposition current density was controlled at 15 mA / cm². 2The duration was 8 minutes. After electrodeposition, the working electrode was removed from the immersion solution and immersed in a pre-prepared complexing solution for electropolymerization. The electropolymerization current density was set to 0.2 mA / cm². 2 The reaction time was 20 min. After the electropolymerization reaction was completed, the working electrode was removed from the complexing solution and thoroughly cleaned with ethanol to remove residual reactants and impurities on the surface. The cleaned electrode was then placed in a drying oven and dried at 80°C for 6 h to obtain the zinc-bromine battery cathode material. Comparative Example 1

[0025] The difference between this comparative example and Example 1 is that the volume ratio of oxygen to argon in step (1) is 1:1. Comparative Example 2

[0026] The difference between this comparative example and Example 1 is that the volume ratio of oxygen to argon in step (1) is 1:8. Comparative Example 3

[0027] The difference between this comparative example and Example 1 is that the organic carbon source in step (1) is benzene. Comparative Example 4

[0028] The difference between this comparative example and Example 1 is that ammonia calcination was not performed in step (3). Comparative Example 5

[0029] The difference between this comparative example and Example 1 is that aniline was not added in step (5). Comparative Example 6

[0030] The difference between this comparative example and Example 1 is that the electropolymerization current density in step (6) is 0.1 mA / cm². 2 The time is 30 minutes. Comparative Example 7

[0031] The difference between this comparative example and Example 1 is that the electropolymerization current density in step (6) is 5 mA / cm². 2 The time is 10 minutes.

[0032] Performance testing: The efficiency performance of the positive electrodes prepared in Examples 1-4 and Comparative Examples 1-11 was tested respectively. The electrolyte was 2.5 mol / L zinc bromide + 3 mol / L potassium chloride + 0.8 mol / L 1-methyl-1-ethylpyrrolidine bromide, the separator was a microporous polyolefin membrane, and the charge / discharge current density was 20 mA / cm². 2 The discharge cutoff voltage is 0.6V. The performance test data of the battery's average coulombic efficiency (CE), voltage efficiency (VE), and energy efficiency (EE) are shown in Table 1.

[0033] Wherein, CE = (amount of charge released during discharge / amount of charge input during charging) × 100%. CE reflects the proportion of charge actually used to output electrical energy during the charging and discharging process to the amount of charge input during charging, reflecting the impact of internal side reactions, charge loss, and other factors on battery performance.

[0034] VE = (Battery operating voltage during discharge / Theoretical voltage) × 100%. VE reflects the effective utilization of the actual output voltage of the battery during charging and discharging relative to the voltage applied during charging, and reflects the influence of factors such as internal polarization on battery performance.

[0035] EE = CE × VE = (Released Energy / Stored Energy) × 100%. EE reflects the battery's overall ability to convert stored chemical energy into electrical energy and output it effectively.

[0036]

[0037] from Figure 1 It can be clearly observed that the zinc-bromine battery cathode material of the present invention adopts a multi-level composite structure design: a three-dimensional porous carbon material treated by plasma cleaning, oxygen / argon etching and chemical vapor deposition is used as the substrate framework. This substrate has a hierarchical pore structure of micropores and mesopores, which provides the material with excellent conductive network and mechanical stability, meeting the working requirements of zinc-bromine flow batteries at high current densities. On this three-dimensional porous carbon substrate, a disordered polyhedral array with a hexahedral geometry is grown by hydrothermal method and ammoniation treatment. These polyhedral units have sharp edges and smooth crystal face features. Furthermore, Sn-Bi bimetallic nanoparticles of 5-20 nm are uniformly distributed on the substrate surface, polyhedral surface and interstices by electrodeposition technology. Finally, a dense complex protective layer is formed on the material surface by electropolymerization process, constructing a multi-functional synergistic system composed of conductive framework, catalytic polyhedron, active nanoparticles and protective layer.

[0038] Analysis of Examples 1-4 and the data in Table 1 shows that the cathode material prepared by this invention exhibits excellent performance in zinc-bromine batteries. Specifically, the coulombic efficiency of the example group (96.2-96.7%) is significantly higher than that of the comparative group (75.7-92.2%), with a maximum improvement of 27.7%, indicating that the example material has a significant advantage in suppressing side reactions such as bromine shuttle. In terms of voltage efficiency, the example group (85.8-86.6%) is generally better than the comparative group (77.0-83.5%), indicating that the example material has better cathode reaction kinetics and lower internal resistance. The difference in energy efficiency is the most significant, with the example group (82.5-83.7%) being up to 25.3% higher than the comparative group (58.4-76.7%), demonstrating outstanding comprehensive performance advantages and fully proving the excellent performance of the cathode material of this invention in zinc-bromine battery applications.

[0039] A suitable oxygen / argon ratio is key to achieving synergistic etching effects: In Comparative Example 1, when oxygen / argon = 1:1, it indicates excessive oxygen plasma etching, causing the microporous structure in the carbon-based three-dimensional conductive network substrate to be enlarged into mesopores / macropores (reduced specific surface area), resulting in the loss of bromine-active materials and a decrease in the bonding strength between porous carbon and the carbon-based three-dimensional conductive network substrate, exacerbating the bromine shuttle effect and the risk of structural detachment; while in Comparative Example 2, when oxygen / argon = 1:8, it indicates that the physical bombardment effect of argon is too high, resulting in a significant reduction in oxygen-containing functional groups on the surface of the carbon-based three-dimensional conductive network substrate and an increase in contact angle (deterioration of hydrophilicity), which cannot effectively suppress the free diffusion of polybrominated ions and cause a decrease in electrolyte wetting rate, ultimately resulting in a 9% reduction in energy efficiency compared to Example 1. Compared with Example 1, the reason for the poor performance of Comparative Example 3 is that when benzene is used as the carbon source for vapor deposition in step (1), its benzene ring structure is prone to generating a highly graphitized carbon layer, resulting in insufficient micropores and low surface polarity, such as Figure 3 As shown, its porosity is lower than that of Example 1 ( Figure 2 This structural characteristic cannot meet the requirements of zinc-bromine battery cathode materials for bromine adsorption, ion transport, and structural stability, ultimately leading to the deterioration of the electrochemical performance of Comparative Example 3. In addition, this scheme did not select complex gases such as multi-carbon organic molecules, because their high hydrogen-to-carbon ratio and uncontrollable decomposition pathways easily lead to the non-directional generation of carbon and the introduction of by-product pollution. In contrast, the organic gas used in the example achieves performance optimization through a controllable pore structure.

[0040] Compared to Example 1, step (3) in Comparative Example 4 did not involve ammonia calcination. As a result, when the cathode material was applied to a zinc-bromine battery, the battery CE test data decreased from 96.7% to 75.7%, the VE test data decreased from 86.6% to 77.1%, and the EE test data decreased from 83.7% to 58.4%. This indicates that the unnitrided metal oxide nanocrystal array has low catalytic activity for the bromine redox reaction and cannot effectively promote the electrochemical reaction kinetics. Secondly, the conductivity of metal oxides is generally lower than that of the corresponding nitrides, which increases the resistance of the cathode material and leads to increased battery polarization. Compared with oxides, metal nitrides usually have better chemical stability and corrosion resistance, and can better maintain structural integrity in the zinc-bromine battery electrolyte. Oxides that have not been treated with ammonia are more likely to dissolve or degrade during long-term cycling. These factors together lead to the cathode material prepared in Comparative Example 4 being significantly inferior to the metal nitride nanocrystal array / three-dimensional porous carbon composite material treated with ammonia in terms of CE, VE, and EE.

[0041] Analysis of Example 1 and Comparative Example 5 shows that Comparative Example 5 did not add aniline for electropolymerization in step (5), resulting in the failure to form a conductive polyaniline modification layer on the surface of the cathode material, thus causing performance defects: First, the absence of the polyaniline layer caused the material to lose its ability to adsorb polybrominates, significantly aggravating the bromine shuttle effect and causing a significant reduction in coulombic efficiency; Second, the polyaniline layer lost its protective effect on metal nitride nanocrystals and Sn-Bi bimetallic nanoparticles, making the active components more likely to detach from the substrate during cycling.

[0042] Compared to Example 1, Comparative Example 6, using an excessively low electropolymerization current density, extended the polymerization time (30 min), but the aniline monomer oxidation polymerization rate was too slow, resulting in a discontinuous polyaniline-bromine complex layer with poor structural stability and weak charge transport capabilities. Comparative Example 7, using an excessively high electropolymerization current density, resulted in a polyaniline-bromine complex layer with excessive cross-linking and numerous structural defects. This dense but disordered polyaniline-bromine complex layer not only reduced the diffusion rate of bromide ions but also caused cracking and detachment during cycling due to internal stress accumulation. In contrast, the optimized electropolymerization current density range used in Example 1 ensured a suitable polymerization rate for orderly polymer chain growth, achieving efficient adsorption of polybrominates and rapid charge transfer, ultimately resulting in significantly improved energy efficiency.

[0043] The specific embodiments described above provide a further detailed explanation of the present invention; however, these descriptions should not be construed as limiting the invention. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a positive electrode material for a zinc-bromine flow battery, characterized in that, Includes the following steps: (1) The carbon-based three-dimensional conductive network substrate is cleaned by inert gas plasma. After cleaning, oxygen / argon plasma is introduced for etching. Then, the etched carbon-based three-dimensional conductive network substrate is subjected to chemical vapor deposition of carbon. The organic gas carbon source used is alkanes, alkenes or alkynes to obtain a three-dimensional porous carbon substrate. (2) The three-dimensional porous carbon substrate is immersed in a mixed aqueous solution containing transition metal salt, hydrolysis ammonia-producing precipitant and neutral or weakly alkaline salt mineralizer for hydrothermal treatment, and then washed and dried with deionized water or ethanol to obtain metal oxide nanocrystal array / three-dimensional porous carbon precursor. (3) Under an ammonia atmosphere, the metal oxide nanocrystal array / three-dimensional porous carbon precursor was calcined to obtain the metal nitride nanocrystal array / three-dimensional porous carbon precursor. (4) Dissolve tin salt, bismuth salt and complexing additive in acidic aqueous solution to obtain a homogeneous soaking solution; (5) Dissolve aniline and bromine source in acidic aqueous solution to obtain a homogeneous complex solution; (6) The homogeneous soaking solution is deposited onto the surface of the metal nitride nanocrystal array / three-dimensional porous carbon precursor by electrochemical deposition. The deposited precursor is then soaked in a homogeneous complexing solution for electropolymerization. Finally, it is washed and dried with deionized water or ethanol to obtain the zinc-bromine flow battery cathode material.

2. The method for preparing the zinc-bromine flow battery cathode material according to claim 1, characterized in that, In step (1), the carbon-based three-dimensional conductive network substrate is one of carbon fiber felt, graphite felt, carbon cloth, and carbon paper; the inert gas plasma is argon or nitrogen; the plasma cleaning power is 200-300W, and the cleaning time is 5-10min; the volume ratio of oxygen to argon is 1:3-5; the plasma etching power is 300-500W, and the etching time is 20-60min; the alkane, olefin, or alkyne organic gas carbon source is one of methane, ethane, ethylene, and acetylene; the alkane, olefin, or alkyne organic gas carbon source flow rate is 20-60mL / min; the vapor deposition carbon temperature is 750-850℃, and the time is 1-4h.

3. The method for preparing the zinc-bromine flow battery cathode material according to claim 1, characterized in that, In step (2), the transition metal salt is one of titanium chloride, aluminum chloride, and zinc nitrate; the hydrolysis ammonia-producing precipitant is one or more of hexamethylenetetramine and urea; and the neutral or weakly alkaline salt mineralizer is one of sodium chloride, potassium chloride, and sodium acetate. The concentration of the transition metal salt is 0.05–0.2 M, the molar ratio of the transition metal salt to the hydrolysis ammonia-producing precipitant is 1:3.5–7, the molar ratio of the transition metal salt to the neutral or weakly alkaline salt mineralizer is 1:1.5–4, the hydrothermal treatment temperature is 150–180 °C, and the time is 5–8 h.

4. The method for preparing the zinc-bromine flow battery cathode material according to claim 1, characterized in that, In step (3), the calcination temperature is 700-900℃ and the time is 1-3h.

5. The method for preparing the zinc-bromine flow battery cathode material according to claim 1, characterized in that, In step (4), the tin salt is stannous sulfate or stannous chloride, the bismuth salt is bismuth nitrate or bismuth chloride, the complexing additive is one of sodium citrate, ethylenediaminetetraacetic acid, or ammonium fluoride, and the acidic aqueous solution is an aqueous solution of sulfuric acid or hydrochloric acid; the molar concentration of the bismuth salt is 0.05-0.15 M, the molar ratio of bismuth salt to tin salt is 1:1-3, the molar ratio of the complexing additive to bismuth salt is 1:3-10, and the molar concentration of acid in the acidic aqueous solution is 0.5-1.5 M.

6. The method for preparing the zinc-bromine flow battery cathode material according to claim 1, characterized in that, In step (5), the bromine source is one of tetrabutylammonium bromide, sodium bromide, and potassium bromide, and the acidic aqueous solution is one of sulfuric acid and hydrochloric acid aqueous solution; the molar concentration of aniline is 0.05-0.2M, the molar ratio of bromine source to aniline is 1:4-8, and the molar concentration of acidic aqueous solution is 0.5-1M.

7. The method for preparing the zinc-bromine flow battery cathode material according to claim 1, characterized in that, In step (6), the electrodeposition current density is 5-15 mA / cm² and the time is 5-10 min; the electropolymerization current density is 0.2-1 mA / cm² and the time is 10-30 min.

8. The application of a zinc-bromine flow battery cathode material prepared by the preparation method according to any one of claims 1 to 7, characterized in that, The zinc-bromine flow battery cathode material described above is used as the cathode material in a zinc-bromine flow battery.

Citation Information

Patent Citations

  • Method for modifying zinc-bromine battery positive electrode material by using ionic liquid bromine complexing agent

    CN119108566A

Cited By

  • Flow battery electrode for improving cycling stability and electrochemical performance and preparation method

    CN121748411A

  • A composite electrode material for zinc-bromine flow battery and preparation method and battery thereof

    CN122494689A